Thermodynamic properties of duplex DNA containing a site-specific d(GpG) intrastrand crosslink formed by an antitumor dinuclear platinum complex - Hofr, C; Farrell, N; Brabec, V (Nucleic acids research, 2001)
Bifunctional polynuclear platinum compounds represent a novel class of metal-based antitumor drugs which are currently undergoing preclinical development. A typical agent is [(trans-PtCl(NH(3))(2))(2)H(2)N(CH(2))(4)NH(2)]Cl(2) (1,1/t,t), which coordinates to bases in DNA and forms various types of covalent crosslinks. It also forms a 1,2-d(GpG) intrastrand adduct, the equivalent of the major DNA lesion of 'classical' cisplatin. In the present study differential scanning calorimetry and spectroscopic techniques were employed to characterize the influence of this crosslink on the thermal stability and energetics of 20 bp DNA duplexes site-specifically modified by 1,1/t,t. Thermal denaturation data revealed that the crosslink of 1,1/t,t reduced thermal and thermodynamical stability of the duplex noticeably more than that of 'classical' cisplatin. The energetic consequences of the intrastrand crosslink at the d(GG) site are discussed in relation to the structural distortions induced by this adduct in DNA and to its recognition and binding by HMG domain proteins. It has been suggested that the results of the present work are consistent with different DNA binding modes of cisplatin and polynuclear bifunctional DNA-binding drugs, which might be relevant to their distinct biological effectiveness.
Keywords: reagencia zkříženě vázaná; diferenciální skenovací kalorimetrie; teplota; Circular Dichroism; Oligodeoxyribonucleotides; Spectrophotometry, Ultraviolet; Mutagenesis, Site-Directed; entropie; Guanine; terciární struktura proteinů; cirkulární dichroismus; adukty DNA; Nucleic Acid Denaturation; Base Sequence; Protein Structure, Tertiary; Temperature; Cross-Linking Reagents; guanin; Binding Sites; mutageneze cílená; Calorimetry, Differential Scanning; oligodeoxyribonukleotidy; denaturace nukleových kyselin; Entropy; protinádorové látky; platina; Antineoplastic Agents; High Mobility Group Proteins; DNA-Binding Proteins; DNA Adducts; sekvence nukleotidů; spektrofotometrie ultrafialová; cisplatina; proteiny s vysokou pohyblivostí; Cisplatin; termodynamika; vazebná místa; Platinum; DNA vazebné proteiny; Thermodynamics